The effects of decision aid structural restrictiveness on decision-making outcomes - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2011)
Decision aids are often designed to direct decision-makers' attention to potential problems or solutions prompted by the decision aid; but in most instances, it is impossible to prompt all possible issues that should be considered in making a decision. Decision aids can induce decision-making biases whereby users focus only on the issues identified by the decision aid and fail to adequately consider other issues that are not identified by the decision aid. The purpose of this study is to investigate whether restricting how users interact with computerized decision aids affects their performance by limiting their ability to consider other possible problems that may not be prompted by the decision aid. Decision aids often restrict the way a user interacts with a decision aid by the rules embedded within computerized decision aids. A more restrictive design imposes more limits on users by forcing users to adapt their decision-making process to match the decision aid. An experiment was conducted by varying the differential effect of both a more restrictive and less restrictive decision aid on users' decision-making outcomes. Results indicate that more restrictive decision aid affects users' decision-making process by increasing their decision-making bias through reducing their ability to identify items not specifically prompted by the aid. This study shows that the degree of restrictiveness is an important aspect of decision aid design and has implications for both future research and practice.